Designing a Content-Addressable Memory Cell Using Multiplexer in Quantum-Dot Cellular Automata. (1st May 2022) - Bagheri, Tohid; Rasouli Heikalabad, Saeed; Jabbehdari, Sam
Abstract : Low power consumption, high density, regularity, and high speed are readily applicable to QCA. Therefore, memory is well suited for implementation using this technology. Because Content Addressable Memory (CAM) is a special type of memory structure used in very fast search applications, QCA can be used to design this memory at the nanoscale. In this paper, we introduce a new structure for the CAM cell. For this purpose, all the components needed to implement this memory cell are designed separately. In order to provide a structure with fewer gates, the operational equations of the components are considered in a way that they can be implemented by a unique multiplexer gate. For this purpose, a new multiplexer is used, which operates based on the Columbic interaction of cells. QCADesigner is used to simulate the proposed structures and verify their operation. The proposed structure has a 28% improvement in the number of cells and a 27% improvement in the occupied area.